Beauty and Body Image Concerns Among African American College Women. (December 2015) - Awad, Germine H.; Norwood, Carolette; Taylor, Desire S.; Martinez, Mercedes; McClain, Shannon; Jones, Bianca; Holman, Andrea; Chapman-Hilliard, Collette
The current study examined body image concerns among African American women. In recent years, there has been an attempt to include ethnic minority samples in body image studies, but few specifically examine unique issues pertaining to beauty and body image for African American college-age women. A total of 31 African American women participated in one of five focus groups on the campus of a large Southwestern University to examine beauty and body image. Data were analyzed using a thematic approach and several themes were identified. The majority of themes pertained to issues related to hair, skin tone, body type, and message sources. Themes included sacrifice, ignorance/racial microaggressions, validation and invalidation by others, thick/toned/curvy as optimal, hypersexualization, and being thin is for White women. Findings of the current study suggest a reconceptualization of body image for African American women where relevant characteristics such as hair and skin tone are given more priority over traditional body image concerns often associated with European American women.